Antibacterial Activities Of Capsicum Frutescens Extracts On Bacteria Isolated From Domestic Food Wastes In Akure - Isaac, Ayodele; Ajibulu, Ajibulu; Oluyomi, O (Department of Technology of Agricultural product (THP) Jambi University, 2020)
The aim of this experiment was to determine the antibacterial actions of the extracts of Capsicum frutescens on Forty four (44) bacteria associated with domestic food wastes in Akure metropolis, Ondo State, Nigeria. The bacteria were subjected to antibacterial test using unfiltered extract (UFE) and filtered extract (FE) of Capsicum frutescens prepared by grinding and filtering long pepper fruits in sterile distilled water in a ratio 1:2 (w/v) in mortal, pestle and Whatman paper by Agar Well Diffusion Methods. The aqueous extracts of C. frutescens showed strong appreciable antibacterial activity against the entire test bacteria. The unfiltered extract demonstrated better antibacterial action over the filtered extract. The zones of inhibition exhibited by UFE and FE were 3.33±0.33 mm to 6.00±0.58 mm and 1.33±0.58 mm to 3.33±0.33 mm. Hence, widest and least inhibitions were observed against Proteus mirabilis, Bacillus licheniformis, Myroids odoratimimus and Proteus vulgaris.